BACTERIAL AND SENSITIVITY PATTERN OF PATHOGENS CAUSING VENTILATOR-ASSOCIATED PNEUMONIA IN INTENSIVE CARE UNIT - Bambang Pujo Semedi; Marsheila Harvy Mustikaningtyas; Kuntaman, Kuntaman (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlight:1. Antimicrobial resistance bacteria isolated from VAP patients are often associated with high mortality and length of hospital stay. 2. Mortality in VAP patients was 33.3% and the VAP group had a longer hospital stay compared to the non-VAP group. 3. The three most predominant bacteria that were found were A. baumannii, P. aeruginosa, K. pneumoniae. Cefoperazone-sulbactam, meropenem and amikacin were more than 70% sensitive against these bacteria.Abstract:Background: Ventilator-Associated Pneumonia (VAP) is the most common nosocomial infection in Intensive Care Unit (ICU). Antimicrobial resistant bacteria isolated from VAP patients are often associated with high mortality and length of hospital stay. Objective: This study aimed to analyze the pattern and sensitivity among pathogens that caused VAP in ICU. Materials and Methods: The study was conducted retrospectively by extracting the data of bacterial isolates from sputum specimens in the Laboratory of Clinical Microbiology, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia and confirming the clinical data on patients suffering from VAP in ICU ward. The study started from January until December 2017. Results: The total 148 pathogens were isolated, 18 of them were diagnosed as VAP, and 130 were not VAP. The most predominant isolates in the VAP group were Acinetobacter baumannii as many as 38 (9%) followed by Pseudomonas aeruginosa 22 (2%), E. coli 16 (7%), and Klebsiella pneumoniae 11 (1%). The pathogens showed a sensitivity rate above 70% to cefoperazone-sulbactam (SCF), meropenem (MEM) and amikacin (AK). Mortality in VAP patients was 33.3% and the VAP group had a longer hospital stay compared to non-VAP group. Conclusion: The three most predominant bacteria that were found were A. baumannii, P. aeruginosa, K. pneumoniae. The pathogens had sensitivity rate above 70% to cefoperazone-sulbactam, meropenem, and amikacin.